Do plantio à colheita: formação em extensão universitária para TAEs no CCR - Alchieri, Douglas Vicente (2022)
This master’s degree dissertation is linked to PPPG - Program of Post Graduation in Public Policies and Educational Managing, from CE - Center of Education, from the Federal University of Santa Maria (UFSM), to the line of research LP2 - Pedagogic Managing and Innovation in Basic Education, and to GEPE - Group of Study and Research of Special Education and Inclusion, and has as a theme the universitary extension in the scope of Technical-Administrative workers in Education of the Center of Rural Science (CCR) from the Federal University of Santa Maria (UFSM). The extension, together with the teaching and the research, make up the trio that constitutes the Brazilian public university. The university, in turn, is made up of students, professors and administrative staff in education, all responsible for developing activities that cover all areas of university performance. However, when looking at the percentage of TAE servers at UFSM and hat percentage of these servers who participate in university extension projects, is verified that participation is small. This work is the result of the research of the Professional Master in Public Policies and Educational Management at the Federal University of Santa Maria UFSM), where the. The author sought to identify which factors motivate and which factors discourage participation in university extension projects of the TAEs servers of the Rural Sciences Center (CCR) of the UFSM. During the research of this master's degree, it was found that TAE servers have interest in participating in extension projects, but they are limited by factors such as: lack of stimulus from the bosses, overwork and difficulties in reconciling their work at UFSM with the workload required for the project. Many servers also claimed to be unaware of this possibility and do not feel qualified at the moment to coordinate extension projects. To the at the same time, the interest of these servers in acting as extensionists within of their areas of knowledge. This dissertation presents as an intervention proposal the elaboration of an extension course aimed at the extensionist training of the TAEs of CCR/UFSM,aimed at presenting the basic concepts of university extension, institutional policies and national university extension programs, the administrative structures that organize and encourage the extension and guidelines for designing and implementing an extension project. This course will be organized in modules, structured in the format of everyday themes of rural sciences, in order to bring the participants closer and make the participants belong to the course.